(untitled) (Ann Arbor, 1997)
On the basis of rich empirical analyses of East and Southeast Asia, and with theoretical insights from different approaches in the social sciences, Culture and Economy addresses these issues in both macroscopic and microscopic terms. Specific topics discussed range from the use and reinvention of Confucian and Islamic legacies in South Korea and Malaysia to promote a particular vision of the economy, to the role of family- and network-structured firms and the reliance on trust-based personal networks in Southeast Asia, to the cultures of labor and management in Chinese village enterprises and Vietnamese ceramics firms, as well as in South Korean export processing zones and the current Chinese labor market.
Keywords: Capitalism,Chủ nghĩa tư bản